Preoperative Statin Exposure Reduces Periprosthetic Fractures and Revisions following Total Knee Arthroplasty - Sax, Oliver C.; Bains, Sandeep S.; Chen, Zhongming; Douglas, Scott J.; Nace, James; Delanois, Ronald E. (The Journal of Knee Surgery, 2022)
The purpose of this study is to examine patients undergoing primary total knee arthroplasty (TKA) with and without prior history of statin use. We specifically evaluated (1) 90-day to 2-year periprosthetic fractures, (2) revisions, and (3) respective risk factors. We queried a national, all-payer database for patients undergoing primary TKA between 2010 and 2020. Chronic statin exposure was then identified and defined as more than three prescriptions filled within 1 year prior to TKA (statin users). A control cohort of patients undergoing TKA without the prior history of statin use was then created (statin naïve). Cohorts were matched 1:1 based on age range, Charlson Comorbidity Index, sex, diabetes, obesity, and tobacco use, yielding 579,136 patients. Multivariate logistic regression was performed to evaluate the risk factors for periprosthetic fractures and revisions, adjusted for demographics and comorbidities. Statin users had a lower incidence of periprosthetic fractures from 90 days to 2 years compared with the statin naïve (p < 0.001). Similarly, statin users had a lower incidence of revisions at 90 days to 2 years (p < 0.001). Using the statin-naïve cohort as a reference, statin use was independently associated with decreased odds of periprosthetic fractures and revisions. Statin use was associated with a reduced risk of periprosthetic fractures and revisions. These results may mitigate postoperative risks though statin therapy is currently not recommended for fracture-related benefits alone.
Keywords: statin; periprosthetic fracture; total knee arthroplasty; arthroplasty